The viscount who lived down the lane ebook Rhymes with love. - Boyle, Elizabeth (Rhymes with Love, 2014)
In New York Times bestselling author Elizabeth Boyle's fourth novel in the Rhymes With Love series, a resolute young woman goes toe-to-toe with the Beast of Mayfair She has no desire for love . . . As she arrives in Mayfair, Louisa Tempest is horrified when her incorrigible cat bolts from the carriage and dashes into a neighbor's house, where she comes face-to-face with the reclusive Viscount Wakefield. But even more dismaying than his foul temper is the disarray in which she finds his home. Convinced his demeanor would improve if his household were in order, Louisa resolves to put everything to rights. . . . until she meets the viscount who lives down the lane Much to his chagrin, Wakefield finds it impossible to keep the meddling Louisa out of his home, invading his daily life with her "improvements," and his nights with the tempting desires she sparks inside him. Wounded in the war, he's scorned society ever since his return . . . until Louisa opens the door to his heart and convinces him to give love a second chance.